Ultrastructural destruction of neurovascular unit in experimental cervical spondylotic myelopathy - Li, Guang-Sheng; Wang, Xu-Xiang; Tan, Ron-Bang; Wang, Kang-Heng; Hu, Xiao-song; Hu, Yong (Frontiers in Neuroscience, 2022)
The pathogenesis of cervical spondylotic myelopathy (CSM) remains unclear. This study aims to explore the ultrastructural pathology of neurovascular unit (NVU) during natural development of CSM. A total of 24 rats were randomly allocated to control group and CSM group. Basso Beattie Bresnahan (BBB) scoring and somatosensory evoked potentials (SEP) were used as functional assessments. Hematoxylin-eosin (HE), toluidine blue (TB) and Luxol fast blue (LFB) stain were used for general structure observation, and transmission electron microscopy (TEM) for ultrastructural characteristics. The evident compression caused significant neurological dysfunction, which was confirmed by the decrease in BBB score and SEP amplitude, as well as the prolongation of SEP latency (P < 0.05). The histopathological findings verified significant decrease in the amount of Nissl body and myelin area, and increase in vacuolation compared to control group (P < 0.05). The TEM results revealed ultrastructural destruction of NVU in several forms, including: neuronal degeneration and apoptosis; disruption of axonal cytoskeleton (neurofilaments) and myelin sheath, and dystrophy of axonal terminal with dysfunction mitochondria; degenerative oligodendrocyte, astrocyte and microglial cell inclusions with degenerating axon and dystrophic dendrite; swollen microvascular endothelium and loss of tight junction integrity; corroded basement membrane and collapsed microvascular wall; proliferated pericyte and perivascular astrocytic endfeet. In the CSM group, reduction was observed in the amount of mitochondrial with normal appearance and the number of cristae per mitochondria (P < 0.05), while no substantial drop of synaptic vesicle number was seen (P > 0.05). Significant narrowing of microvascular lumen size was also observed, accompanied by growth in vascular wall area, endothelial area, basement membrane thickness, astrocytic endfeet area, and pericyte coverage area (rate) (P < 0.05). Altogether, the findings of this study demonstrated ultrastructural destruction of NVU in experimental CSM model with dorsal-lateral compression, revealing one of the crucial pathophysiological mechanisms of CSM.